Evaluation of the complete profile of male partners in infertile couples with special emphasis on detection of genital tuberculosis - Sethi, Niharika; Guleria, Karandeep; Verma, Devender; Tempe, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: To evaluate the complete profile of male partners in infertile couples with special emphasis on detection of genital TB. Methods: The study was conducted in the fertility clinic of department of obstetrics and gynaecology, Maulana Azad Medical College and Associated Lok Nayak and GB Pant Hospitals, New Delhi from August 2015 to December 2016 among 100 infertile couples. Detailed history, general physical and local examination of male partners was done. Routine blood and urine tests, combined with radiology examination of chest and mantoux skin test of male partners were done followed by investigations specific to male factor evaluation. Two semen samples collected after 3-5 days of sexual abstinence were analyzed to assess semen parameters such as volume, total sperm count, total motility and morphology. Ultrasound and colour Doppler of scrotum and hormone analysis was done in all cases of azoopermia, oligoasthenospermia or asthenospermia. Testicular FNAC was done for all cases of azoospermia and oligoasthenospermia to establish cause of male infertility. Results: 72% couples had primary infertility. 34% males were daily tobacco chewers. 8 males had varicocele and 2 had undescended testes on examination. 60% males had semen analysis in the normal range and 19% had azoospermia. Tobacco chewing, testicular size abnormalities, varicocele, hydrocele were significantly associated with abnormal semen findings. A statistically significant relation was found between elevated S.FSH and semen analysis findings. A statistically significant association was found between penile meatal stenosis, chest X-ray, mantoux test with history of TB in male/female partner. Conclusions: Primary infertility was more common than secondary infertility in our study group. Addiction was found to be an important factor in infertile men particularly tobacco chewing. Elevated Serum FSH levels were a common finding in males with azoospermia and oligoasthenospermia.